Analyze this [videorecording (DVD)] - Ramis, Harold; Ramis, Harold; De Niro, Robert; Crystal, Billy; Kudrow, Lisa; Viterelli, Joe, 1937-2004; Palminteri, Chazz (Warner Home Video, 1999)
A spoof on the gangster roles that have been associated with De Niro's film career, this is the story of an anxiety-ridden Mafia boss who monopolizes the services of a family psychiatrist.